Wokół mitów dotyczących adaptacji kulturowej narzędzi diagnostycznych - Hornowska, Elżbieta; Paluchowski, Władysław Jacek (About myths associated with test adaptation process, 2006)
An increasing number of educational, and psychological tests are being adapted for use in other languages and cultures. Substantially more test translations and adaptations can be expected in the future because international exchanges of tests have become more common, and interest in crosscultural psychology and international comparative studies of achievement has grown. It should be recognized that translated and adapted tests and instruments are nearly always going to be different than the source language versions. The goal then should be to minimize the differences to acceptable semantic, psychometric, linguistic, and psychological levels. There are a number of myths associated with test adaptation that appear in measurement practice. These myths are widespread, undermine effective test adaptation initiatives, and have its consequences in the validity of adapted tests decreasing. Adapted tests may have limited value unless they are adapted with a high degree of concern for issues of usability, reliability and validity. In the paper, the main myths (mainly originating from adaptation and translation process identification), the examples of typical mistakes and procedures of their elimination are described. Adapted tests will have limited value unless they are adapted with a high degree of concern for issues of usability, reliability and validity. Avoiding the five myths described in this paper should go a long way toward improving current practices.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 468-476